In planta proximity dependent biotin identification (BioID) - Madiha Khan (Nature Portfolio, 2018)
Abstract Proximity dependent biotin identification (BioID) has emerged as a powerful tool for studies of proteome architecture, including insoluble or membrane-associated proteins. The technique has been well established in mammalian cells but has yet to be applied to whole plant systems. Here we demonstrate the application of BioID on leaf tissues of the model plant Arabidopsis thaliana, thereby expanding the versatility of this important technique and providing a powerful proteomics tool for plant biologists.